2022-RA-1609-ESGO Pre-operative risk factors of concomitant endometrial carcinoma in women with hysteroscopic diagnosis of complex atypical hyperplasia: a multicenter study. (20th October 2022) - Vargiu, Virginia; Rosati, Andrea; Capozzi, Vito Andrea; Baroni, Alessandro; Palmieri, Emilia; Perrone, Emanuele; Berretta, Roberto; Cosentino, Francesco; Scambia, Giovanni; Fanfani, Francesco
Abstract : Introduction/Background: Approximately 40% of complex atypical hyperplasia (CAH) are finally upstaged to invasive endometrial carcinoma (EC).The aim of this study was to identify pre-operative variables that can predict the presence of concomitant EC at final histopathological analysis, so as to identify a population at increased risk of EC and to help the clinician in the preoperative and surgical management of patients with CAH. Methodology: Multicenter-retrospective analysis of patients with pre-operative diagnosis of CAH who underwent total hysterectomy. Study population have been divided according to final histopathological examination into Group-1 (including patient with final diagnosis of benign condition or CAH) and Group-2 (including patient with final diagnosis of EC). Results: A total of 460 patients have been retrieved. Group-1 included 243 patients while Group-2 217.The following pre-operative variables resulted as significant predictors of EC at univariate analysis: older age (51–64 years: OR 2.140, p=0.001, ≥65 years: OR 2.140, p=0.001), post-menopausal condition (OR 1.644, p=0.012), the presence of comorbidities (OR1.497, p=0.032), the abnormal uterine bleeding (AUB) (OR:1.647, p= 0.011), the diagnosis of endometrial thickening as a pre-operative ultrasound (US) feature (OR:3.569, p<0.001) and an endometrial thickness ≥20 mm at pre-operative US (OR: 2.735, p<0.001). At multivariate analysis the age between 51–64 years, the diagnosis of endometrial thickening during US-scan and the US identification of an endometrial thickness ≥20 mm were confirmed as independent risk factors for concomitant EC (age 51–64 yr OR:1.823, p=0.040, US endometrial thickening OR:3.122, p<0.001, US endometrial thickness ≥20 mm OR:1.958, p=0.010) ( table 1 ). Conclusion: Perimenopausal women with diagnosis of CAH, a pre-operative US diagnosis of endometrial thickening together with an endometrial thickness ≥ 20 mm should be considered at high risk of concomitant EC at final histological examination.Gynecologist should consider these factors when counselling these patients and tailoring the surgical strategy, possibly considering the need for nodal evaluation.